Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis. (February 2023) - Liang, Rong-Zhen; Luo, Cong; Liu, Yuan; Hu, Wan-Li; Guo, Yi-Hang; Yu, Hai-Xia; Lu, Ting-Ting; Chen, Shu-Quan; Zhang, Xiu-Juan; He, Xin-Hua
Abstract: The CO/COL gene family plays an important role in regulating photoperiod-dependent flowering time in plants. In this study, two COL2 gene homologs, MiCOL2A and MiCOL2B, were isolated from 'SiJiMi' mango, and their expression patterns and functions were characterized. The MiCOL2A and MiCOL2B genes both belonged to the group Ⅰ of CO/COL gene family. MiCOL2A and MiCOL2B exhibited distinct circadian rhythms and were highly expressed in leaves during the flowering induction period. Subcellular localization analysis revealed that MiCOL2A and MiCOL2B are localized in the nucleus. The overexpression of MiCOL2A and MiCOL2B significantly delayed flowering time in Arabidopsis under both long-day (LD) and short-day (SD) conditions. The MiCOL2A and MiCOL2B overexpression Arabidopsis plants exhibited more tolerance to slat and drought stress after abiotic stress treatments, with greater ROS scavenging capacity and protective enzyme activity, less cell damage and death and higher expression of stress response genes than wild type plants. Bimolecular fluorescence complementation (BiFC) analysis showed that MiCOL2A and MiCOL2B interacted with several stress-related proteins, including zinc finger protein 4 (MiZFP4), MYB30-INTERACTING E3 LIGASE 1 (MiMIEL1) and RING zinc finger protein 34 (MiRZFP34). The results indicate that MiCOL2A and MiCOL2B are not only involved in flowering time but also play a positive role in abiotic stress responses in plants. Highlights: Two CONSTANS-like 2 genes were cloned from mango. The expression patterns of the CONSTANS-like 2 genes were analysed in mango. Overexpression of two CONSTANS-like 2 in Arabidopsis resulted in delayed flowering. Overexpression of two CONSTANS-like 2 enhanced the salt and drought stress tolerance in transgenic Arabidopsis.